Information and communications technology and financial development as catalysts for gender equality in Brazil’s agricultural sector - Letong, Freiderick Yohanna (Managing global transitions, 2025)
In this study, we examined the effects of information and communications technology (ICT) and financial development on mitigating gender inequality in Brazil, using autoregressive distributed lag (ARDL) approaches, between 1991 and 2022. The ARDL bounds test was employed to find the presence of co-integration within the series of data. Both in the short run and the long run, financial development has a significant negative impact on gender disparity; this means that policies aimed at enhancing women’s financial and consumption services should be promoted in the short run. In the long run, we can conclude that ICT developments lead to a decreasein gender inequalities, which may imply the need for strategic, long-term planning to increase ICT infrastructure, especially in deprived areas. This includes subsidising affordable internet, skills training for women in the ICT field, and promoting women’s participation in the technology industry. In addition, the impact of optimal financial development varies over time; hence, there is a need for flexibility and sustainability in financial development. Policy makers should therefore continue to strengthen and enhance financial inclusion initiatives, as well as regularly follow up on the impact of these initiatives on gender equality.
Keywords: agriculture; financial development; finančni razvoj; gender inequality; human capital index; indeks človeškega kapitala; informacijska in komunikacijska tehnologija; information and communications technology; kmetijstvo; neenakost spolov